2017
DOI: 10.20517/2347-8659.2017.50
|View full text |Cite
|
Sign up to set email alerts
|

Altered filamin A enables amyloid beta-induced tau hyperphosphorylation and neuroinflammation in Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is a neurodegenerative disease with proteopathy characterized by abnormalities in amyloid beta (Aβ) and tau proteins. Defective amyloid and tau propagate and aggregate, leading to eventual amyloid plaques and neurofibrillary tangles. New data show that a third proteopathy, an altered conformation of the scaffolding protein filamin A (FLNA), is critically linked to the amyloid and tau pathologies in AD. Altered FLNA is pervasive in AD brain and without apparent aggregation. In a strikin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Our results correlate with previous findings showing accumulation and increased levels of NFAT isoforms in post-mortem brains from patients with AD, which further suggest that changes in NFAT levels contribute to AD progression; 62 The fact that they found increase of NFAT in both early and late stage of the disease suggests that our early molecular findings are linked to the later disease mechanism as well. Other recent studies also showed an increase of NFAT-1 in a different transgenic AD mouse model 63 , and a third proteopathy for AD, suggests that an alteration of the scaffolding protein FILAMIN-A, is critically linked to the amyloid and tau pathologies in AD and leads to increased tau phosphorylation 64 . Another study showed that FILAMIN-A inhibitors decrease P-Tau and amyloid-beta aggregates 65 .…”
Section: Discussionmentioning
confidence: 85%
“…Our results correlate with previous findings showing accumulation and increased levels of NFAT isoforms in post-mortem brains from patients with AD, which further suggest that changes in NFAT levels contribute to AD progression; 62 The fact that they found increase of NFAT in both early and late stage of the disease suggests that our early molecular findings are linked to the later disease mechanism as well. Other recent studies also showed an increase of NFAT-1 in a different transgenic AD mouse model 63 , and a third proteopathy for AD, suggests that an alteration of the scaffolding protein FILAMIN-A, is critically linked to the amyloid and tau pathologies in AD and leads to increased tau phosphorylation 64 . Another study showed that FILAMIN-A inhibitors decrease P-Tau and amyloid-beta aggregates 65 .…”
Section: Discussionmentioning
confidence: 85%
“…Filamin A has been reported to interact with more than 90 functionally diverse range of cellular proteins, including adhesion proteins, transmembrane receptors, transcription proteins, and signaling molecules, thus making it a key component of the host cell signaling scaffold (Savoy and Ghosh, 2013;Wang et al, 2015;Burns and Wang, 2017). In general, high-throughput virus-host interactomes revealed that viral proteins show preferential interaction with proteins having high number of direct interacting partners; making FLNA an interesting target of study (Dyer et al, 2008;Komarova et al, 2011;Munier et al, 2013;de Chassey et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The former process mobilizes various mechanisms that are toxic to neurons [26] , and the second results in destabilization of microtubules and dysfunction of the cytoskeleton and of axonal transport [27] . Both processes, acting synergistically, lead to neuritic, synaptic and neuronal loss, through a vicious circle of interconnecting final pathways of oxidative stress, excitotoxicity, mitochondrial dysfunction, apoptosis and Ca 2+ -mediated cell death [28][29][30] , while prion-like spread [31] and neuroinflammation [32][33][34] are increasingly recognized as important early mechanisms.…”
Section: Established (Core) Csf Biomarkers Of Admentioning
confidence: 99%